Efficacy and safety of low doses of beta-blocker agents combined with amiodarone in refractory ventricular tachycardia - Tonet, J; Frank, R; Fontaine, G; Grosgogeat, Y (Pacing and clinical electrophysiology, 1988)
Twenty patients aged 55 +/- 16 years with 40 chronic ventricular tachycardias (VT) refractory to 4.6 +/- 1.9 antiarrhythmic drugs, used alone or in combination, were managed by low doses of beta-blocker agents combined with oral amiodarone (Am), either after loading (1.2 g for 7 days, n: 5) or reloading (1.2 g for 4 days, n: 15) of Am. All patients proved refractory to Am alone. Seven VT were also refractory to endocardial catheter fulguration in six patients. Thirteen patients had coronary artery disease, three had arrhythmogenic right ventricular dysplasia, two had dilated cardiomyopathy, one had valvular disease, and one had no structural heart disease. Ten patients had an EF less than 30%. Ten patients were in NYHA functional class three. VT was permanent in three patients, daily in three, weekly in seven, paroxysmal in seven. In 11 patients, VT occurred both at day and night. In 11 patients, decrease of the sinus cycle preceeded VT. Oral administration of a daily low dose of a beta blocker agent (acebutolol 100 mg, betaxolol 5-10 mg, metoprolol 50 mg, nadolol 20-40 mg, pindolol 2.5 mg, propanolol 30 mg, sotalol 80-160 mg, terta-tolol 2.5 mg) combined with 400 mg/day of Am suppressed VT episodes in all patients. None presented heart failure or collapse. The mean reduction of the heart rate was 15% (65 to 55/min). At discharge, exercise ECG (n: 14) induced non sustained VT in two patients. At programmed electrical stimulation (PES) (n: 15), VT was no longer inducible in 4 patients, was slower, well-tolerated in nine patients, and remained inducible at the same rate in only two patients.